Means and Ends The Idea of Capital in the West, 1500-1970 - Boldizzoni, F.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Capital has dominated the imagination of Western society from the Industrial Revolution. Means and Ends offers the first comprehensive interpretation of the rise, evolution and crisis of this concept from the sixteenth century to the modern day. Based on a wealth of primary sources it offers an exciting study of intellectual and cultural history.
Keywords: Civilization—History.; Economic history; Economic theory; World history; Social history; Cultural History; Economic History; History of Economic Thought/Methodology.; Economic Theory/Quantitative Economics/Mathematical Methods; World History, Global and Transnational History; Social History